2008
DOI: 10.1109/jstsp.2008.2006718
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal and Multi-Tissue Measures of Connectivity Revealed by Joint Independent Component Analysis

Abstract: The human brain functions as an efficient system where signals arising from gray matter are transported via white matter tracts to other regions of the brain to facilitate human behavior. However, with a few exceptions, functional and structural neuroimaging data are typically optimized to maximize the quantification of signals arising from a single source. For example, functional magnetic resonance imaging (FMRI) is typically used as an index of gray matter functioning whereas diffusion tensor imaging (DTI) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 70 publications
0
34
0
Order By: Relevance
“…Application of a purely data-driven method (joint ICA [jICA]) to combine information from both the functional connectivity and WM connectivity has demonstrated that the functional connectivity in the DMN is highly dependent on the WM integrity of the corpus callosum connecting the two hemispheres. (Franco et al, 2008). The genu of the corpus callosum was reported to play an important role interconnecting different regions of the DMN in a recent study reconstructing the WM pathways between functionally connected brain regions forming resting-state networks (van den Heuvel et al, 2009a).…”
Section: Constrained Source-based Morphometrymentioning
confidence: 99%
See 3 more Smart Citations
“…Application of a purely data-driven method (joint ICA [jICA]) to combine information from both the functional connectivity and WM connectivity has demonstrated that the functional connectivity in the DMN is highly dependent on the WM integrity of the corpus callosum connecting the two hemispheres. (Franco et al, 2008). The genu of the corpus callosum was reported to play an important role interconnecting different regions of the DMN in a recent study reconstructing the WM pathways between functionally connected brain regions forming resting-state networks (van den Heuvel et al, 2009a).…”
Section: Constrained Source-based Morphometrymentioning
confidence: 99%
“…An integrated analysis of the sMRI GM data and DTI WM data will enrich our understanding of the brain structural networks. It has been increasingly reported in several studies that combining multimodal imaging provides a richer representation of the brain connectivity (Franco et al, 2008;Greicius et al, 2009;Skudlarski et al, 2008;Teipel et al, 2010). With the aid of the newly introduced concept of the DTI connectivity, a significant overall agreement was achieved by comparing the quantified anatomical connectivity with resting-state functional connectivity (Skudlarski et al, 2008), which provides a powerful validation for the representation of neuronal connectivity by resting-state correlations.…”
Section: The Relationship Between the Structural Network And The Varimentioning
confidence: 99%
See 2 more Smart Citations
“…Usually these maps are coupled together by a shared loading parameter. Joint ICA have been used in fusing couples of the modalities (fMRI-sMRI (GM) [16][17][18], fMRI-EEG [19][20][21][22], fMRI-DTI (FA) [23,24], GM-WM [25]). In this paper Joint ICA was applied on two modalities fMRI and EEG of both healthy and Schizophrenia patients to jointly compare the features of each of them together to find some features that can describe the nature of the Schizophrenia.…”
Section: Joint Independent Component Analysis (Joint Ica)mentioning
confidence: 99%